1981
DOI: 10.1007/bf01834811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different nitrogen levels, plant population and soil nutrient status on yield and yield components of maize (Zea mays L.) in different ecological zones of Nigeria

Abstract: Field studies on the effect of nitrogen levels, plant population and soil nutrient status on maize yield and yield components at eight different sites representing six different ecological maize growing zones of Nigeria conducted during 1976Nigeria conducted during , 1977Nigeria conducted during and 1978 indicated that N significantly influenced yield at six of the eight sites, NIFOR, Umudike and Uyo (rain forest zone), Mokwa and Samaru (Savanna zone) and Riyom (derived savanna zone). Optimum N required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The optimum nitrogen required for successful yam production on Alfisols that have been cultivated for at least two years was shown to be 35 kg ha" 1 , but there was no response to applications of phosphorus or potassium despite the wide variation in soil ^ status, thus confirming the work of Irving (1956) and Vanderzaag et al (1980). The significant correlation of tuber yield with soil nitrogen and potassium content suggests that soil nutrient status can exert a significant influence on crop yield, as shown for maize by Kayode and Agboola (1981). Obigbesan (1973) reported that applications of potassium significantly increased dry matter accumulation and starch content of cassava, but in this study on yam large applications of potassium had no significant effect on starch content although they reduced dry matter accumulation.…”
Section: Physical and Chemical Characteristics Of The Experimental Somentioning
confidence: 48%
“…The optimum nitrogen required for successful yam production on Alfisols that have been cultivated for at least two years was shown to be 35 kg ha" 1 , but there was no response to applications of phosphorus or potassium despite the wide variation in soil ^ status, thus confirming the work of Irving (1956) and Vanderzaag et al (1980). The significant correlation of tuber yield with soil nitrogen and potassium content suggests that soil nutrient status can exert a significant influence on crop yield, as shown for maize by Kayode and Agboola (1981). Obigbesan (1973) reported that applications of potassium significantly increased dry matter accumulation and starch content of cassava, but in this study on yam large applications of potassium had no significant effect on starch content although they reduced dry matter accumulation.…”
Section: Physical and Chemical Characteristics Of The Experimental Somentioning
confidence: 48%
“…Planting of maize at high densities had been found to require correspondingly high rates of N (Lucas and Sagbohan, 1984). Also for effective utilization of N by maize, time and frequency of application had been found to be important (Kayode and Agboola, 1981). In this study, the range of density used was wide enough to bring out the actual relationship between total dry matter yield per unit area and density of planting and total grain yield per Downloaded by [University of Aberdeen] at 23:38 27 December 2014 hectare and density of planting.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported the effect of crude oil on the soil and the capacity of some organic manure in the remediation of oil polluted soils (Kayode & Agboola 2003). Although several methods have been used to remediate soils contaminated with inorganic chemicals, the recent is the use of micro-organisms (James et al 1996) through a process called Bioremediation (Sasikumar & Taniya 2003).…”
Section: Introductionmentioning
confidence: 99%